Thrombus composition and efficacy of thrombolysis and thrombectomy in acute ischaemic stroke - Jolugbo, Precious (Stroke, 2021)
Thrombi retrieved from patients with acute ischaemic stroke (AIS) are highly heterogeneous. Recent data suggest that thrombus composition may impact on mechanical thrombectomy, the number of recanalization manoeuvres, resistance to retrieval, and on thrombolytic potential. Our aim was to summarise evidence describing the impact of thrombus composition on efficacy of mechanical thrombectomy and thrombolysis in patients with AIS. The scoping review methodology guided by the Joanna Briggs Institute, an adaption of the Arksey and O’Malley, was followed. Comprehensive searches were conducted in MEDLINE, EMBASE, SCOPUS and Web of Science. Articles were classified into four key themes: (i) composition of stroke thrombi; (ii) thrombus composition and mechanical thrombectomy; (iii) thrombus composition and thrombolytic therapy; (iv) novel imaging and endovascular approaches. Our search identified 698 articles published from 1987 to June 2020. Additional articles were extracted from reference lists of the selected articles. Overall, 95 topic-specific articles identified for inclusion published in 40 different journals were included. Reports showed that thrombus composition in stroke was highly heterogeneous, containing fibrin, platelets, red blood cells (RBC), von Willebrand Factor (vWF), and neutrophil extracellular traps. Thrombi could roughly be divided in fibrin- and RBC-rich clots. Fibrin-rich clots were associated with increased recanalization manoeuvres, longer procedure time and less favourable clinical outcomes compared RBC-rich clots. Advances in detection or treatment of thrombi that take into account clot heterogeneity may be able to improve future endovascular and thrombolytic treatment of stroke.